2023
DOI: 10.3390/brainsci13111503
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Receptor Agonists and Related Mental Health Issues; Insights from a Range of Social Media Platforms Using a Mixed-Methods Approach

Davide Arillotta,
Giuseppe Floresta,
Amira Guirguis
et al.

Abstract: The emergence of glucagon-like peptide-1 receptor agonists (GLP-1 RAs; semaglutide and others) now promises effective, non-invasive treatment of obesity for individuals with and without diabetes. Social media platforms’ users started promoting semaglutide/Ozempic as a weight-loss treatment, and the associated increase in demand has contributed to an ongoing worldwide shortage of the drug associated with levels of non-prescribed semaglutide intake. Furthermore, recent reports emphasized some GLP-1 RA-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 112 publications
3
6
0
Order By: Relevance
“…Consistent with this, responses to cues predicting food rewards in VTA DA axons and basal amygdala neurons in hungry mice were strongly attenuated following satiation [46]. Sem-related decreased levels of food cravings reported by subjects prescribed with this molecule have been associated with earlier attainment, in Sem-related subjects, of food satiety [47,48]. This may occur because GLP-1 mimetics show pro-dopaminergic efficacy [49], and as a result can modulate reward [50].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Consistent with this, responses to cues predicting food rewards in VTA DA axons and basal amygdala neurons in hungry mice were strongly attenuated following satiation [46]. Sem-related decreased levels of food cravings reported by subjects prescribed with this molecule have been associated with earlier attainment, in Sem-related subjects, of food satiety [47,48]. This may occur because GLP-1 mimetics show pro-dopaminergic efficacy [49], and as a result can modulate reward [50].…”
Section: Discussionsupporting
confidence: 53%
“…This behaviour of misuse may arguably be occurring in both obese (e.g., through forged and/or diverted prescriptions) and healthy, non-obese individuals due to unrealistic ideals of physical attractiveness [51]. Although intake of Sem has not been associated with a stimulant-like 'high', a rebound syndrome may occur after abrupt Sem cessation [47].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported a range of experiences from people using GLP-1RAs, including both positive effects on mood and negative experiences such as heightened anxiety and difficulty sleeping. 8 Real-world pharmacovigilance analysis has not shown a disproportionate increase in suicide/self-injury events overall associated with GLP-1RAs, but nuances exist, with a reported increase in children (OR: 2.50, 95%CI 1.02-6.13, p = .05). 6 Moreover, post hoc pooled data analysis from randomized controlled trials of liraglutide, a GLP-1RA, showed similarly low rates of depression and anxiety between the liraglutide and placebo groups but did reveal a small numerical imbalance in suicidal ideation among liraglutide users.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the impact of GLP-1 RAs on mental health outcomes is complex, due to both the subjects’ individual differences and potential biases in data analysis [ 20 , 21 , 22 ]. Moreover, both obesity and type 2 diabetes are multifactorial and complex diseases, and their exact inter-relationship with mental health and addiction are not fully understood, including the psychopathological issues linked to food-related emotional and behavioral aspects [ 1 , 21 ]. Other unclear aspects may involve the interconnection between GLP-1 receptors and a range of cognitive-, immunological-, and inflammation-related issues [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…These methods, initially used mainly in marketing and social sciences, have recently attracted increasing levels of interest in the scientific community, given both the obvious difficulties/limitations in carrying out clinical trials and the partial inadequacy of data that can be collected in clinics. Hence, “netnography”, when combined with content analysis and qualitative and quantitative analysis [ 21 , 30 ], may offer intriguing opportunities to better understand the patterns of substance use. When used with extreme care and constant human control, the vast amount of web data have also opened the door to the use of machine learning and generative artificial intelligence (AI) as interpretive and analytical support tools [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%